The Acceptability of System in Assessing the Student’s Attendance using Image Processing - B. Maravillas, Alme (International Journal of Advanced Engineering, Management and Science, 2021)
Student’s attendance is vital in any academic institution as students are the primary stakeholders. There are different means of checking attendance, one of these is automated checking through scanning student’s id card using image processing. In Bohol Island State UniversityClarin, there is a system that asses the student’s attendance. It is a system that automatically counts the number of students who entered in the premises. This system uses image processing to monitor the attendance by scanning the student id card through a live camera. The system automatically identified the faces of the student with their corresponding id numbers. Thus, the purpose of this study is to assess the acceptability level of thesystem in assessing the attendance. The researcher conducted a survey regarding the system’s acceptability on the 200 students that were composed of 100 females and 100 males. It was calculated based on the number responses that the overall weighted mean of the system’s acceptability in terms of perceived ease of use and perceived usefulness was 4.1 While the overall standard deviation is 0.58 which means the respondents, who rated the system has a unanimous perception of Very Acceptable. With these results, the researcher concluded that the system is easy to use and useful to the institution since it can monitor accurately the number of logs.